Transferability of Human Capital and Immigrant Assimilation – An Analysis for Germany - Leilanie Basilio; Thomas K. Bauer (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
This paper investigates the transferability of human capital across countries and the contribution of imperfect human capital portability to the explanation of the immigrant-native wage gap. Using data for West Germany, our results reveal that, overall, education and labor market experience accumulated in the home countries of the immigrants receive significantly lower returns than human capital obtained in Germany. We further find evidence for heterogeneity in the returns to human capital of immigrants across origin countries. Finally, imperfect human capital transferability appears to be a major factor in explaining the wage differential between natives and immigrants.
Keywords: J61; J31; J24; 330; Human capital; rate of return; immigration; assimilation; Humankapital; Wissenstransfer; Migranten; Bevölkerung; Bildungsertrag; Soziale Integration; Lohnstruktur; Schätzung; Deutschland